The Effects of Online Formative and Summative Assessment on Test Anxiety and Performance: A Study Among First-Year Undergraduate Students at A Higher Education Institution in Abu Dhabi, United Arab Emirates - ALSUWAIDI, MUNA (2019)
The presented study was conducted to provide greater insight into the potential positive, neutral and/or negative effects of online formative and summative assessment on test anxiety and performance. The aim of the study was to determine if online assessment could address the problems associated with test anxiety, which include poor study habits, distraction during testing, mental blocks and other physiological and psychological effects that students might experience as a result of perceived test threats. The theoretical frameworks that the study was based on were constructivism, behaviorism and multiple intelligences, as well as the constructs of Assessment for Learning, blended learning and self-paced learning. Past research on online formative and summative assessment has found that online testing and practice tests can reduce test anxiety because the conditions that facilitate test anxiety are reduced through the integration of online practice tests. In other words, students feel more confident in their knowledge and testing abilities, which in turn removed some of the pre-established, perceived test threats. The current study was carried out using a qualitative, case study approach, in which 24 students and one instructor in a first year, undergraduate social sciences general education class at a large Higher Education Institution in Abu Dhabi, United Arab Emirates. The students were given two online tests, one without access to a prior online practice test, and one with access to a prior online practice test. The test scores were compared and used as supplemental quantitative data to the qualitative data collected from open-ended questionnaires. The questionnaires were modeled after the UTAUT2 technology use and acceptance model, which examines performance expectancy, effort expectancy and social influence as indicators of behavioral intention to use and accept online assessment systems. After conducting the qualitative and quantitative analyses, it was found that the students had more confidence in their test-taking abilities because they had access to the online practice test. This confidence resulted in decreased instances of test anxiety and scores all around improved on the second test. It can be concluded from the results of this study that teachers can help motivate their students to study by using online practice tests, which will in turn help reduce test threats and improve academic outcomes.